Density-independent calibration functions for nondestructive moisture sensing in flowing grain. Issue 2 (3rd April 2019) - Trabelsi, Samir; Lewis, Micah A.; Nelson, Stuart O.
Abstract: In many agricultural and industrial applications, moisture content needs to be determined in real time while the material is moving. For granular and particulate materials, density-independent calibration functions were used in microwave moisture sensors to minimize the effect of bulk density changes. Three of these calibration functions expressed in term of the attenuation, phase shift and the dielectric properties were investigated for moisture determination in flowing grain and seed samples. To simulate in the laboratory measurements on flowing grain, a flowing system was designed and assembled. The flowing-grain system consisted of a conical stainless steel hopper connected to a polycarbonate chute and an iris diaphragm-type valve placed at the bottom. The iris can be manually adjusted to provide different flow rates. The flowing system was calibrated by using static samples which were placed in the polycarbonate chute between two patch antennas operating at 5.8 GHz and connected to a vector network analyzer. Measurements at room temperature on grain and seed samples flowing at varying flow rates showed that moisture content can be predicted with density independent calibration functions with a standard error of performance (SEP) of less than 1% moisture content.